Association between Serum Magnesium Level and Depression in Selective Serotonin Reuptake Inhibitors Treated Major Depressive Disorder Patients - Sultana, Sarmin; Anwar Sonia, Sadia Binte; Rumu, Humayra; Jhumu, Sumayra; Wahid, Sumaiya Binte; Chowdhury, Iftekhar Hossain (Mugda Medical College Journal, 2025)
Depression, a common mental health disorder, contribute to burden globally as well as in Bangladesh despite availability of many treatment modalities. Evidence showed improvement of depressive symptoms after magnesium supplementation but could not report consistent significant results. A randomized, double-blind, placebo-controlled trial was conducted in Bangladesh Medical University (BMU), Dhaka, Bangladesh, between March 2020 and January 2022, to relate serum magnesium with the level of depression. Serum magnesium level was estimated by using spectrophotometric method in Beckman Coulter autoanalyzer (AU 680) at Department of Biochemistry & Molecular Biology of the same institution. Level of depression was measured using Bangla Version of the Depression Anxiety Stress Scale 21 items (DASS- 21)-BV. In this randomized controlled trial on 90 moderate and severe major depressive disorder (MDD) patients, respondents were given a treatment of 200 mg of magnesium glycinate or placebo tablets twice daily orally for the 8 weeks with selective serotonin reuptake inhibitors (SSRIs). Between 2020 and 2022, serum magnesium level was measured as the primary indicator at baseline, and after 8 weeks of intervention. DASS-21-BV was completed as the primary outcome at baseline and 8 weeks intervention. The study found a difference in serum magnesium from baseline to 8 weeks (p<0.05) and from the control arm (p<0.05). As serum magnesium was increased from baseline, DASS-21 items were decreased from baseline to 8 weeks (r= –0.6). The results of the regression suggested that serum magnesium explained 38% of the variance and significantly predicted DASS-21 (–12.37 points/mg/dL; t= –4.79; p=0.00). In this trial, lower serum magnesium levels were found to be linked to depressive symptoms suggesting serum magnesium may help identify the biological basis of depressive symptoms and select patients who could respond to magnesium supplementation. Mugda Med Coll J. 2025; 8(2): 138-144